2020
DOI: 10.1089/dia.2019.0244
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention to Reduce Hypoglycemia Fear in Parents of Young Kids with Type 1 Diabetes Through Video-Based Telemedicine (REDCHiP): Trial Design, Feasibility, and Acceptability

Abstract: Background: Fear of hypoglycemia (FH) is common in parents of young children with type 1 diabetes (T1D) and problematically linked to maladaptive behaviors to avoid low blood glucose, parenting stress, and burnout. This study examined the feasibility and acceptability of a novel group-based telemedicine intervention to reduce FH in parents of young children with T1D. Materials and Methods: Forty-three families of a young child with T1D (1-6 years of age; diagnosed with T1D for at least 6 months) enrolled in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 25 publications
(29 reference statements)
1
44
0
3
Order By: Relevance
“…While discussions about remote telemedicine are rapidly increasing due to the pandemic, a number of studies have previously investigated the potential benefits of telemedicine in diabetes care. 6,9,10 In a systematic review of 29 studies in the field of paediatric diabetes care, 7 it was concluded that telemedicine has the potential to facilitate patient monitoring and can improve short-term glycaemic control in some contexts. It has also been suggested that virtual diabetes care may prove effective in aiding behavioural change, as well as providing social and psychological support.…”
Section: Discussionmentioning
confidence: 99%
“…While discussions about remote telemedicine are rapidly increasing due to the pandemic, a number of studies have previously investigated the potential benefits of telemedicine in diabetes care. 6,9,10 In a systematic review of 29 studies in the field of paediatric diabetes care, 7 it was concluded that telemedicine has the potential to facilitate patient monitoring and can improve short-term glycaemic control in some contexts. It has also been suggested that virtual diabetes care may prove effective in aiding behavioural change, as well as providing social and psychological support.…”
Section: Discussionmentioning
confidence: 99%
“…as being discussed face-to-face. Recent studies have shown that telemedicine in diabetes care might improve self-management, therapy engagement, and metabolic outcomes [1,3,4]. It is assumed that patients and diabetes teams have positive attitudes about video consultation if they have the means to set it up technically and carry it out.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos futuros podem testar intervenções que visem melhorar o LS das mães sobre o manejo das situações de urgência. Experiências prévias no ensino de outros tópicos de suporte de vida mostram que o uso de aulas teórico-práticas e de simulação realística pode empoderar as mães para o cuidado da criança em urgências 23,24 .…”
Section: Discussionunclassified